Pragmatics of Eco-compassion in Angelic Speech Therapy: An Effective Communication Strategy for Individuals with Serious Mental Illness - P., Angelicdolly; Sanjaya, Ridwan; Wibhowo, Christin; Soetomo, Greg.; Adiseputra, Nicholaus; Murniati, Cecilia Titiek; Dukut, Ekawati Marhaenny (Celt: A Journal of Culture, English Language Teaching & Literature, 2024)
Misunderstanding and misperception in communication often occur due to listeners’ failure to grasp the accurate meaning of a speaker’s utterances. These failures are typically caused by a lack of pragmatic competence in understanding the contexts and conditions of speakers when interacting with listeners in specific situations. An example of communication failure is seen with individuals experiencing serious mental illness (ISMI). Communicating and interacting with ISMI is challenging due to their communication disorders. Their speech and behavior are often impacted by hallucinations, delusions, disorganized talk and abnormal thought processes. This study aimed to explore effective communication strategy to deal with ISMI. The case study involved 3 (three) ISMI who met the eligibility criteria. An inductive qualitative method employing participant observation and documentary analysis was used. Data collection included primary, secondary and tertiary sources, which were triangulated with in-depth interviews with their families. Data analysis was conducted through thematic coding, which revealed that pragmatic competence (80%), Compassionate Psychiatric Care (CPC; 15%) and ecological conduciveness (5%) are key factors in improving communication fluency with ISMI. This article concludes that the speech therapy method developed by Angelicdolly, which combines pragmatic principles with compassion for the ecological conduciveness of ISMI is an effective strategy for enhancing communication with these individuals.